Secondary structure of the internal transcribed rDNA (ITS) regions of cosmopolites sordidus (Germar) and odoiporus longicollis (Olivier): a first report in family Curculionidae - Kumar, Lalitha Sunil (International Journal of Tropical Insect Science, 2019)
In the present work the consensus secondary structure of the internal transcribed rDNA spacers ITS1 and ITS2 of two weevils i.e. Cosmopolites sordidus (Germar) and Odoiporus longicollis (Olivier) has been described. The secondary structures of the ITS1 region of C.sordidus and O.longicollis have ten and five helices respectively, emerging from a central core. Two and five helices emerge from a central core in the ITS2 secondary structures of C.sordidus and O.longicollis respectively, and do not conform to the `paneukaryotic' four domain model. The ITS2 sequences of these two weevils share three regions with maximum sequence identity. Of these, two are present at the 5' and 3' end and share structural similarity, suggesting their possible role in the processing of the rRNA. This is the first report of the secondary structure of the ITS region in family Curculionidae which can serve as a valuable resource for homology modelling and phylogenetic studies.
Keywords: Cosmopolites sordidus (Germar); Curculionidae; ITS1; ITS2; Odoiporus longicollis (Olivier); Secondary structure